Preparation and CO2 Adsorption Performance of Porous Aluminum Fumarate MOFs Pellet - Lijiao Ma (AIDIC Servizi S.r.l., 2021)
Aluminum fumarate metal organic frameworks (AlFu MOFs) pellet was successfully prepared with outstanding porous structure and its CO2 adsorption performance was investigated. As the binder mass increased, the pellet mechanical strength rose while the CO2 adsorption capacity reduced. The chosen AlFu pellet with 2.5wt% carboxymethyl cellulose sodium (CMC) binder retained the micro-morphology characteristics with a specific surface area of 726.06 m2/g and micropore volume of 0.33 cm3/g. The adsorption performance of CO2 by the pellets was studied at different partial pressures and temperatures. The results showed that the adsorption capacity of CO2 in AlFu pellet was increased with lower adsorption temperature and higher CO2 partial pressure, the maximum adsorption amount was 1.26 mmol/g at 35 °C and 1.0 bar. The CO2 adsorption kinetics and the limiting factors for adsorption rate were analyzed. Compared with pseudo-second order model the pseudo-first order kinetic model can better describe the CO2 physical adsorption behavior of AlFu pellet. The rate-limiting kinetic analysis revealed that the CO2 adsorption rate was determined by film diffusion and intra-particle diffusion rather than inter-particle diffusion.